2013
DOI: 10.1016/j.ijdevneu.2013.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of neural stem cell fate during corticogenesis

Abstract: The cerebral cortex comprises over three quarters of the brain, and serves as structural basis for the sophisticated perceptual and cognitive functions. It develops from common multipotent neural stem cells (NSCs) that line the neural tube. Development of the NSCs encompasses sequential phases of progenitor expansion, neurogenesis, and gliogenesis along with the progression of developmental stages. Interestingly, NSCs steadfastly march through all of these phases and give rise to specific neural cell types in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 118 publications
(184 reference statements)
1
61
0
1
Order By: Relevance
“…Epigenetic regulation includes histone modifications, DNA methylation, and other mechanisms, which work together to establish and maintain the global and local condensed or decondensed chromatin states to determine gene expression [96][97][98] . Disruption of epigenetic machineries is known to provoke aberrant gene expression patterns that give rise to developmental defect.…”
Section: Epigenetic Regulation Of Stem Cell Potentialmentioning
confidence: 99%
“…Epigenetic regulation includes histone modifications, DNA methylation, and other mechanisms, which work together to establish and maintain the global and local condensed or decondensed chromatin states to determine gene expression [96][97][98] . Disruption of epigenetic machineries is known to provoke aberrant gene expression patterns that give rise to developmental defect.…”
Section: Epigenetic Regulation Of Stem Cell Potentialmentioning
confidence: 99%
“…This occurs primarily via histone modification 4 or the action of ATP-dependent chromatin remodeling complexes, such as SWI/SNF (BAF) complexes. [5][6][7][8] In addition, recent studies have shown that DNA methylation 9 and long non-coding RNA (lncRNA)-based mechanisms 10 also contribute to the complexity of epigenetic regulation during development.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Smad1/5/9 signaling actively instructs the development and differentiation of distinct neural lineages from human pluripotent stem cells and neural stem cells at the border between the epidermis and the neural plate. 15,17 In addition, differentiation into a neural lineage can be induced by the IL-6 family of cytokines [e.g., leukemia inhibitory factor (LIF) and ciliary neurotrophic factor and bone morphogenic protein (BMP) family cytokines (e.g., BMP2 and BMP4)], which activate distinct downstream transcription factors such as STAT3 and Smad1.…”
Section: Introductionmentioning
confidence: 99%
“…15,17 In addition, differentiation into a neural lineage can be induced by the IL-6 family of cytokines [e.g., leukemia inhibitory factor (LIF) and ciliary neurotrophic factor and bone morphogenic protein (BMP) family cytokines (e.g., BMP2 and BMP4)], which activate distinct downstream transcription factors such as STAT3 and Smad1. 14,16,18,19 The receptor kinases, such as TGF-b and BMP, activate Smad1 and STAT3 signaling by phosphorylation as phosphorylation plays a central role in their transcriptional activation bridged by p300. 16,20 Interestingly, the inhibition of tyrosine phosphorylation of STAT3 (at Y705 residue) is mediated by the Smad4-dependent TGF-b signaling.…”
Section: Introductionmentioning
confidence: 99%